Efficacy and safety of dapoxetine in treatment of premature ejaculation: an evidence‐based review. Issue 9 (25th July 2016) - Russo, A.; Capogrosso, P.; Ventimiglia, E.; La Croce, G.; Boeri, L.; Montorsi, F.; Salonia, A.
Summary: Background: Premature ejaculation (PE) is a major issue in male sexual health, with a global prevalence estimated to be between 20% and 40%, making it the most common sexual dysfunction in men. PE causes distress and reduced quality of life for patients and has a negative impact on interpersonal relationships. Historically, it has been treated with cognitive therapy, behavioural methods and off‐label use of selective serotonin reuptake inhibitors (SSRIs) usually used to treat depression and other psychological disorders. Dapoxetine is the only SSRI specifically designed to treat PE. Mechanism of action: Dapoxetine hydrochloride is a potent inhibitor of serotonin reuptake transporters. Dapoxetine is suited for 'on‐demand' treatment of PE because of its rapid absorption and short initial half‐life. Efficacy: Evidence from published studies showed that dapoxetine 30 mg or 60 mg taken 'on‐demand' results in a significant increase in intravaginal ejaculatory latency time (IELT) when compared with placebo. Most patient‐reported outcomes are clearly improved relative to placebo following dapoxetine therapy, indicating greater control over ejaculation, more satisfaction with intercourse, less ejaculation‐related distress and significantly reduced interpersonal difficulties. Safety: The most common adverse events with dapoxetine are nausea, dizziness, somnolence, headache, diarrhoea and insomnia. Usually they do not lead to drug discontinuation. Conclusion: Dapoxetine is the only effective and safe available on‐label oral treatment for PE, and its use can result in better quality of life for the patient and their sexual partner.